1992
DOI: 10.1111/j.1471-4159.1992.tb09304.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fixation in Neuronal and Astroglial Cells in Culture

Abstract: The concentration of potassium in the extracellular fluid has been found to stimulate the rate of CO2 fixation by astroglial cells grown in primary culture. Raising the concentration of extracellular potassium increased both the initial rate of formation of the 14C-labeled products of 14CO2 fixation and the final steady-state level of these products within the cells. In contrast, neither veratridine nor L-glutamate affected the rate of CO2 fixation in astroglial cells. The very low rate of CO2 fixation found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 16 publications
7
50
2
1
Order By: Relevance
“…The authors anticipated a decarboxylating role for the enzyme, although in one study it was shown to possess significant carboxylating activity (Salganicoff and Koeppe, 1968). The view of astrocytes as the only pyruvate-carboxylating compartment in the brain apparently received support from a study on 14 CO 2 fixation in cultured neurons and astrocytes (Kaufman and Driscoll, 1992), which found a much higher 14 CO 2 fixation (i.e., carboxylation) in astrocytes. In that study the radiolabeled metabolites were not identified, however, making it impossible to deduce by which enzymatic pathway the carboxylation occurred.…”
Section: Discussionmentioning
confidence: 97%
“…The authors anticipated a decarboxylating role for the enzyme, although in one study it was shown to possess significant carboxylating activity (Salganicoff and Koeppe, 1968). The view of astrocytes as the only pyruvate-carboxylating compartment in the brain apparently received support from a study on 14 CO 2 fixation in cultured neurons and astrocytes (Kaufman and Driscoll, 1992), which found a much higher 14 CO 2 fixation (i.e., carboxylation) in astrocytes. In that study the radiolabeled metabolites were not identified, however, making it impossible to deduce by which enzymatic pathway the carboxylation occurred.…”
Section: Discussionmentioning
confidence: 97%
“…Inset: time course of effect on glycogenolysis by 10 mmol/L K + during a 20-mins period (modified from Hof et al, 1988). (Hertz, 1973) and found that (i) when glucose was the substrate, either activation procedure caused a stimulation of at least 60%, and (ii) when lactate was the substrate, electrical stimulation increased respiration by only 19% (McIlwain, 1953), whereas K + caused a rise in respiration of 45% to 67% (Ghosh and Quastel, 1954;Takagaki and Tsukada, 1957 Figure 6C), more so at 25 mmol/L (Kaufman and Driscoll, 1992). The response is not affected by ouabain and may represent a direct stimulation of PC, perhaps coordinating neuronal signaling and glutamate synthesis.…”
Section: Fuel For Regulation Of Extracellular K + Concentration By Asmentioning
confidence: 99%
“…For instance, it has been shown that glutamine synthesis (Hayashi et al, 1988;Mearow et al, 1990) and glutamate uptake by astrocytes (Voisin et al, 1993), on the one hand, and glutamate synthesis and release from granule cells (Westergaard et al, 1991), on the other hand, are modulated by the presence of granule cells and astrocytes, respectively. Moreover, cooperativity between neurons and astroglia for CO, fixation has been proposed by Kaufman and Driscoll (1992). The use of sophisticated systems of coculture as those reported by Westergaard et al (1991) opens the possibility of investigating whether such modulations are mediated by diffusible factors released in the culture medium or by direct contacts between the two cell populations.…”
mentioning
confidence: 95%
“…Such a characterization is the prerequisite before investigating the intercellular modulation of the metabolism. So, metabolic properties specific to glial or neuronal cells have been analyzed by studies with either '"C-labelled glucose and pyruvate (Fitzpatrick et al, 1988), [2-'5N]glutamine (Yudkoff et al, 1988), [1-'"Clglutamate (Farinelli et al, 1992) or '"CO, (Kaufman and Driscoll, 1992). In the present work, we investigated the metabolism of [l -'3C]glucose in both rat cerebellum astrocytes and granule cells in primary cultures.…”
mentioning
confidence: 99%